2011
DOI: 10.1371/journal.pone.0029293
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm-Mycorrhiza Interactions Can Affect the Diversity, Structure and Functioning of Establishing Model Grassland Communities

Abstract: Both earthworms and arbuscular mycorrhizal fungi (AMF) are important ecosystem engineers co-occurring in temperate grasslands. However, their combined impacts during grassland establishment are poorly understood and have never been studied. We used large mesocosms to study the effects of different functional groups of earthworms (i.e., vertically burrowing anecics vs. horizontally burrowing endogeics) and a mix of four AMF taxa on the establishment, diversity and productivity of plant communities after a simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 83 publications
2
35
0
Order By: Relevance
“…It should be noted, however, that water infiltration is highly heterogeneous in space (Hassler et al 2014), and that the experiment was performed in intact soil, rather than in a homogenised substrate. Water infiltration may indeed be unpredictable even under highly controlled conditions: for instance, in a greenhouse experiment that simulated a heavy rainfall event similar to ours (40 mm), anecic earthworms increased water infiltration (Zaller et al 2011), but the effect was not repeatable in a subsequent experiment with similar methodology (Zaller et al 2014).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…It should be noted, however, that water infiltration is highly heterogeneous in space (Hassler et al 2014), and that the experiment was performed in intact soil, rather than in a homogenised substrate. Water infiltration may indeed be unpredictable even under highly controlled conditions: for instance, in a greenhouse experiment that simulated a heavy rainfall event similar to ours (40 mm), anecic earthworms increased water infiltration (Zaller et al 2011), but the effect was not repeatable in a subsequent experiment with similar methodology (Zaller et al 2014).…”
Section: Discussionmentioning
confidence: 68%
“…In particular, earthworms may have improved the availability of N to plants (van Groenigen et al 2014), for instance by incorporating the surface-applied manure into the rhizosphere and releasing N through mucus and casts, stimulating microbial activity and turnover (Postma-Blaauw et al 2006). It is possible that earthworm-enhanced N availability to plants more than compensated for any leaching induced by intense rainfall; but L. terrestris usually increases N losses through leaching (Domínguez et al 2004;Costello and Lamberti 2008;Zaller et al 2011). To ensure that the plants would not be N-limited during the experiment, we had fertilized all the mesocosms with manure more than 1 month before seeding.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of plant species diversity in grasslands has been shown to affect abundance, biomass and activity of earthworms [18-21]. On the other hand, effects of earthworms have been shown to benefit certain plant functional groups more than others [22-25] affecting plant community structure and diversity [26]. The role of earthworms has been most often studied on a single plant species, while only few have investigated effects on plant communities [27-31].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that AMF promoted the growth of the mycotrophic plants (van der Heijden et al, 2003), since Haynes (1980) suggested that T. pratense may be more mycotrophic than L. perenne. In previous studies AMF were found to have positive effects on T. pratense aboveground biomass (Eisenhauer et al, 2009;Zaller et al, 2011b;Sabais et al, 2012). However, studies reported inconsistent results for L. perenne.…”
Section: Discussionmentioning
confidence: 91%